2018
DOI: 10.1021/jacs.8b02271
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Rhodium Complexes with Selective Toxicity toward Mismatch Repair-Deficient Cancers

Abstract: Rhodium metalloinsertors are a unique set of metal complexes that bind specifically to DNA base pair mismatches in vitro and kill mismatch repair (MMR)-deficient cells at lower concentrations than their MMR-proficient counterparts. A family of metalloinsertors containing rhodium-oxygen ligand coordination, termed “Rh–O” metalloinsertors, has been prepared and shown to have a significant increase in both overall potency and selectivity towards MMR-deficient cells regardless of structural changes in the ancillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 42 publications
0
58
0
Order By: Relevance
“…Furthermore, we demonstrated that most compounds were able to inhibit the APE1‐induced cleavage of AP sites in DNA by competing with the enzyme for binding to the substrate, and that the inhibitory activity (as characterized by IC 50 and K I values) was directly related to the affinity and selectivity of ligands to the substrate (i.e., AP site). Beyond direct implications in the context of APE1‐related chemoresistance, these conclusions may be extended to other DNA repair pathways, the DNA substrate of which may represent a target for small‐molecule ligands, such as direct damage reversal and mismatch repair …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that most compounds were able to inhibit the APE1‐induced cleavage of AP sites in DNA by competing with the enzyme for binding to the substrate, and that the inhibitory activity (as characterized by IC 50 and K I values) was directly related to the affinity and selectivity of ligands to the substrate (i.e., AP site). Beyond direct implications in the context of APE1‐related chemoresistance, these conclusions may be extended to other DNA repair pathways, the DNA substrate of which may represent a target for small‐molecule ligands, such as direct damage reversal and mismatch repair …”
Section: Discussionmentioning
confidence: 99%
“…Beyondd irecti mplications in the context of APE1-related chemoresistance,t hese conclusions may be extended to other DNA repair pathways, the DNA substrate of which may represent at arget for small-molecule ligands, such as direct damage reversal [53] and mismatch repair. [54,55] We also demonstrated that deliberate incorporation of substituents into the naphthalenophane scaffold might be exploited to modulate, or totallys uppress,t he intrinsic APsite cleavage activity of ligands (b-a nd b,d-elimination reactions at AP sites). Quite unexpectedly,m ost efficient APsite cleavage waso bserved with the unsubstitutedd ithiaazamacrocycle 2,7-BisNP-S,f ollowed by the rationally designed ligand endowed with two auxiliary nucleophilic groups, 2,7-BisNP-NNH 2 .A lthough the reasons for the particularly high activity of 2,7-BisNP-S are not clear at this point, this observation prompts for af urther systematic and mechanistic study of sulfur-containing DNA ligands as AP site-cleaving agents.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] To understand more fully the potential clinicala pplicability of rhodium metalloinsertors, we examined our mostp otent and selectivem etalloinsertor,[ Rh(phen)(chrysi)(PPO)]Cl 2 (RhPPO, Figure 1), across 27 CRC cell lines (Table S1). [12,13] These cell lines represent ad iverses et of tumors, spanningt he four subtypes of CRC andb oth MMR-and MMR + phenotypes. [14,15] The toxicities of RhPPO,w hich selectively targets MMR deficiencies,a nd the non-selectiveF DA-approved chemotherapeutic cisplatin, which covalently binds the abundant d(GpG) motifs present in all DNA (Figure 1), were assessed in this cell line panel using al uciferase-based luminescence assay which measures ATPf rom living cells.…”
mentioning
confidence: 99%
“…Platinum, palladium,r uthenium, and gold metal complexes have been synthesized by the pharmaceutical industry for an umber of medicinal applicationst hat include antiviral,a ntibacterial, antirheumatic and anti-inflammatory efficacy. [24] Metalswere first used 50 years ago, when cisplatin (cis-diamminedichloroplatinum(II)) was shown to inhibit cellular division in Escherichia coli and was later studied for itsa ntitumor activity. [25,26] Cisplatin has since then,s hown to inhibitP AF-in-duced platelet aggregation.…”
mentioning
confidence: 99%
“…[28,30] Other complexes have not yet entered clinicalt rial due to their high cardiotoxicity. [24] Previouss tudies have shown that metal complexes, such as square planar rhodium(I) organometallic complexes anda series of novel octahedral rhodium(III) complexes possess potent antithrombotic properties. [27] Recently,N HC-based (NHC = N-heterocyclic carbene) complexes have attracted substantiali nterest as these compounds possess broad applications in the field of medicine.…”
mentioning
confidence: 99%